Концепт «родина» по данным беларускоязычных текстов - Руденка, Алена (Slavia Orientalis, 2025)
The article examines the use of names for the concept “homeland” in texts of different types of discourse within Belarusian. Analyzed are contexts with the lexemes radzima, ajchyna, baćkaŭščyna in official documents, scientific texts, folklore, fiction and newspapers as well as in text corpora. A conclusion is drawn about the opposition exiting within the Belarusian worldview of the motherland as a country and the notion of the local homeland. This opposition originates in the formation of the new Belarusian language of the late 19th – early 20th century, when peasant culture stood in opposition to the government, which continued to exist in the Soviet period. The local homeland, home, family were often more important than the bigger one. The latter was usually nominated by the proper noun – Belarus.